2020
DOI: 10.1007/s00247-020-04885-w
|View full text |Cite
|
Sign up to set email alerts
|

Additional value and new insights by four-dimensional flow magnetic resonance imaging in congenital heart disease: application in neonates and young children

Abstract: Cardiovascular MRI has become an essential imaging modality in children with congenital heart disease (CHD) in the last 15–20 years. With use of appropriate sequences, it provides important information on cardiovascular anatomy, blood flow and function for initial diagnosis and post-surgical or -interventional monitoring in children. Although considered as more sophisticated and challenging than CT, in particular in neonates and infants, MRI is able to provide information on intra- and extracardiac haemodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
0
18
0
1
Order By: Relevance
“…The phantom experiment showed that improving 4D flow spatial resolution from 2.4 mm to 1.5 mm improved accuracy. This study used an acquired temporal resolution of 42 msec, similar to earlier studies and guidelines 10,30 . Since increased temporal resolution has been shown to improve accuracy of 4D flow volume assessment, 31–33 differences in temporal resolution might also contribute to the difference in flow volumes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phantom experiment showed that improving 4D flow spatial resolution from 2.4 mm to 1.5 mm improved accuracy. This study used an acquired temporal resolution of 42 msec, similar to earlier studies and guidelines 10,30 . Since increased temporal resolution has been shown to improve accuracy of 4D flow volume assessment, 31–33 differences in temporal resolution might also contribute to the difference in flow volumes.…”
Section: Discussionmentioning
confidence: 99%
“…This means that scan duration can be extensive in patients with complex CHD and highly trained scanner operators are required 9 . Recent developments in three‐dimensional (3D) time‐resolved three‐directional phas‐contrast MRI (four‐dimensional [4D] flow) have enabled shorter scan duration as flows in all vessels of interest are acquired simultaneously and requires minimal slice planning compared to two‐dimensional (2D) flow 10,11 . This shorter scan duration increases the chance of successful study when using feed‐and‐sleep, 12 instead of sedation or general anesthesia.…”
mentioning
confidence: 99%
“…double outlet right ventricle, interstage single ventricles at 4–6 kg) and in smaller vessels (i.e. pulmonary vein flow to measure total pulmonary blood flow in mixing lesions), it becomes important to understand what, if any, advantages contrast agents convey in the assessment of cardiothoracic blood flow using 4D Flow CMR [ 13 , 14 ]. The purpose of this study was to assess the accuracy of 4D Flow CMR (as compared with 2D-PC) in ferumoxytol-enhanced CMR studies compared to gadolinium-enhanced CMR studies in small children with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Neonates bring challenging imaging requirements: high heart and respiratory rates, small cardiovascular structures, and a tendency to ignore instructions. To limit motion and buy additional quiescent imaging time, the use of general anesthesia or sedation are commonly used 2 . Furthermore, exogenous contrast agents are frequently employed to increase signal‐to‐noise, speed up scan time, or increase spatiotemporal resolution.…”
mentioning
confidence: 99%
“…To limit motion and buy additional quiescent imaging time, the use of general anesthesia or sedation are commonly used. 2 Furthermore, exogenous contrast agents are frequently employed to increase signalto-noise, speed up scan time, or increase spatiotemporal resolution. These approaches have enabled assessment of complex congenital heart disease that is unavailable with other imaging modalities.…”
mentioning
confidence: 99%